Dinâmica da regeneração do subsolo de áreas degradadas dentro do bioma Cerrado - Rodrigues, Graciela B. [UNESP]; Maltoni, Kátia L. [UNESP]; Cassiolato, Ana Maria R. [UNESP] (FapUNIFESP (SciELO), 2007)
The objective of this research was to evaluate the physical and chemical conditions of revegetated subsoil in degraded areas in a Cerrado biome and to verify which plants promote better conditions for soil recovery. The research was conducted in the remaining area of the hydroelectrical plant site at Ilha Solteira (SP). The experimental design was a completely randomized with five treatments and three replications. The treatments consisted of: natural regeneration area, brachiaria area, Pinus sp. area, exposed soil area and Cerrado grassland (used as control). The following soil characteristics were appraised: porosity; density, stability of aggregates, infiltration rate, temperature, exchangeable cations, organic matter, pH and potential acidity. The results show that Pinus is not a good species to recover the chemical attributes of the subsoil. The revegetated areas need to be improved in their physical attributes to allow a better development of the vegetation. Brachiaria and the natural regeneration were the most promising treatments, presenting results similar to natural Cerrado.
Dynamics of the subsoil regeneration in degraded areas of Cerrado
Keywords: Brachiaria; Physical soil properties; Pinus; Savanna; Soil fertility